(Invited) Selective Etch of Si and SiGe for Gate All-Around Device Architecture. (11th September 2015) - Wostyn, Kurt; Sebaai, Farid; Rip, Jens; Mertens, Hans; Witters, Liesbeth; Loo, Roger; Hikavyy, Andriy Yakovitch; Milenin, Alexey; Horiguchi, Naoto; Collaert, Nadine; Thean, Aaron; Mertens, Paul W.; et al.
Abstract : The Gate All-Around device architecture requires the formation of semiconductor nanowires. As an example SiGe nanowires can be formed by the selective removal of rSi in a Si-SiGe fin-shaped stack. In this paper we will show how alkaline solutions can be used for the selective removal of Si to SiGe and SiGe to Ge. We will also show that the anisotropy of the SiGe alkaline etch is not an extension of Si, even at low to moderate Ge concentrations (Ge ≤ 50%).